3D carbon foam-supported WS2 nanosheets for cable-shaped flexible sodium ion batteries. Issue 23 (25th May 2018) - Wang, Ye; Kong, Dezhi; Huang, Shaozhuan; Shi, Yumeng; Ding, Meng; Von Lim, Yew; Xu, Tingting; Chen, Fuming; Li, Xinjian; Yang, Hui Ying
Abstract : NGQDs-WS2 /3DCF three-dimensional nanoarchitecture was designed and synthesized as a high-performance flexible and free-standing anode electrode for cable-shaped sodium-ion batteries. Abstract : Sodium ion batteries (SIBs) are proposed as alternatives to the current widely used lithium ion batteries (LIBs) due to the abundance of battery-grade sodium sources in nature. However, the search for suitable high-performance electrode materials for SIBs continues to remain a significant challenge. Herein, we report a hybrid nanoarchitecture with nitrogen-doped graphene quantum dots (NGQDs)-decorated WS2 nanosheets anchored on a porous three-dimensional carbon foam (NGQDs-WS2 /3DCF) scaffold as the anode that enables long-term cycling and high rate capability for SIBs. Benefiting from the 3D robust porous interpenetrating framework and the NGQDs decoration, the NGQDs-WS2 /3DCF nanoarchitecture exhibits a high rate capability with a capacity of 268.4 mA h g −1 at 2000 mA g −1, and a long lifetime with an extraordinary capacity retention of 97.1% over 1000 cycles. Furthermore, the pseudocapacitance contributions of the NGQDs-WS2 /3DCF nanoarchitecture are quantified by an in-depth kinetics analysis, which provides a better understanding of the excellent electrochemical performances. Remarkably, a cable-shaped flexible full SIB was also demonstrated using NGQDs-WS2 /3DCF as the anode electrode, which exhibits high capacity and excellent flexibility. The nanoarchitecture fabrication approach and the surface engineering strategy as well as the demonstrated cable-shaped configuration may open an avenue for the development of wearable SIBs with high performance.